A comunidade de peixes associada às macrófitas aquáticas flutuantes do reservatório de Itá - Rio Uruguai - Brasil - Silva, Samara Hermes (Universidade Federal de São Carlos, 2011)
Different samplings were done in the floating macrophytes stands at Itá reservoir during September, 2006 and March, 2008, with the following objectives: (1) verify the existence of a species-specific relationship between fish species and the floating macrophytes Eichhornia crassipes, Pistia stratiotes e Salvinia sp.; (2) analyze which factors explain the distribution of littoral fish assemblage; and (3) evaluate if the presence of aquatic macrophytes influences the spatiotemporal distribution of fish assemblages in this region. It was observed some fish assemblage segregation between macrophyte stands composed by Eichhornia crassipes and by Salvinia sp., suggesting a strong influence of the macrophyte stand composition on fish assemblage structure. It was also observed a strong preference of the species Gymnotus carapo, Eigenmannia virescens and Hoplias malabaricus for macrophyte stands composed by E. crassipes, reinforcing the existence of a species-specific relationship between some species of fish and of aquatic macrophtyes. In terms of littoral fish distribution, it was observed that, apparently, the presence of the aquatic macrophytes per se is not the only factor influencing the distribution of littoral fish assemblage, which seemed to be taking advantages from low to medium macrophyte stand size, while at maximum stand size, only few species still use this environment. In this way, it is possible to say that the fish assemblage structure of the studied areas at Itá reservoir was influenced by was influenced by the presence of aquatic macrophytes, although significant daily and seasonal fluctuations in the fish community were observed.
Keywords: Ecologia de comunidade de peixes; Macrófitas aquáticas; CIENCIAS BIOLOGICAS::ECOLOGIA